Pengaruh Frekuensi Senam Hamil (Prenatal Yoga) terhadap Penurunan Anxiety pada Primigravida Usia Kehamilan >28 Minggu di Puskesmas Manding - Eka Meiri Kurniyati; Yulia Wardita; Emdat Suprayitno (Health Media, 2023)
Pregnant women who experience psychological disorders are at risk of increasing premature birth by 1.55 times compared to healthy pregnancies, low birth weight, experiencing prolongation of the second stage, impaired immunity, hypertension and postpartum depression. The survey results in January 2023 among 10 pregnant women, 8 people experienced mild anxiety about being sick during the delivery process, 2 people experienced moderate anxiety where they were afraid of dying and afraid of not being able to give birth normally. One effort to overcome psychological disorders in pregnant women is to do pregnancy exercise in the form of prenatal yoga. This study used a pre-experiment with a post-trial design without a control group. The sampling technique is a total sampling of 35 primigravidas who experience anxiety at the Manding Health Center, Kab. Sumenep. Anxiety assessment using the Hamilton Anxiety Rating Scal. The treatment given was prenatal yoga 1x/week for 8 weeks with a duration of 60 minutes and data analysis using the Wilcoxon test. The results of the study showed that there was a decrease in anxiety after doing prenatal yoga. Where before the primigravida treatment, 25 people (71%) experienced moderate anxiety, 10 people (29%) had mild anxiety and those who had no anxiety (0%). After the intervention, the number of primigravidas who experienced moderate anxiety was 15 people (43%), mild anxiety was 11 people (32%) and no anxiety was 9 people (25%). Meanwhile, based on data analysis with the Wilcoxon test (P <0.05) it means that H0 is rejected, meaning there is a decrease in anxiety by doing prenatal yoga. The conclusion from the results of the study is that there is a decrease in anxiety in primigravidas at >28 weeks of gestation at the Manding Health Center. The suggestion for this research is that midwives can integrate prenatal yoga to reduce anxiety in primigravidas